2019
DOI: 10.1002/ece3.5099
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a cryptic barrier in the West Pacific Ocean suggests the effect of glacial climate changes on a widespread sea‐dispersed plant, Vigna marina (Fabaceae)

Abstract: Ocean currents are an important driver of evolution for sea‐dispersed plants, enabling them to maintain reciprocal gene flow via sea‐dispersed diaspores and obtain wide distribution ranges. Although geographic barriers are known to be the primary factors shaping present genetic structure of sea‐dispersed plants, cryptic barriers which form clear genetic structure within oceanic regions are poorly understood. To test the presence of a cryptic barrier, we conducted a phylogeographic study together with past demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…However, fairly equal number of individuals sampled across most of the sites, very low polymorphism, and considering the variation of sample sizes in the estimation of diversity parameters might minimize the biasness generated from the sampling size variation. The ABC analysis is a powerful tool and has been widely used to infer population divergence time for other marine taxa (e.g., Tomizawa et al, 2017 ; Yamamoto et al, 2019 ), the estimates might suffer from uncertainties like generation time of the species, overlapping of generations, and 95% CI of the inferred parameters ( Tsuda et al, 2015 ). However, given the high genetic differentiation and limited evidence of haplotype sharing between populations of distinct regions, the bias of temporal estimates might be limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fairly equal number of individuals sampled across most of the sites, very low polymorphism, and considering the variation of sample sizes in the estimation of diversity parameters might minimize the biasness generated from the sampling size variation. The ABC analysis is a powerful tool and has been widely used to infer population divergence time for other marine taxa (e.g., Tomizawa et al, 2017 ; Yamamoto et al, 2019 ), the estimates might suffer from uncertainties like generation time of the species, overlapping of generations, and 95% CI of the inferred parameters ( Tsuda et al, 2015 ). However, given the high genetic differentiation and limited evidence of haplotype sharing between populations of distinct regions, the bias of temporal estimates might be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Using the cpDNA data, the demographic history of divergence between populations was assessed in the approximate Bayesian computation (ABC) framework implemented in DIYABC ver. 2.0 ( Cornuet et al, 2014 ) following ( Tomizawa et al, 2017 ; Yamamoto et al, 2019 ). We did not use the nSSR data of L. littorea for the ABC analysis due to presence of null alleles (see section Genetic diversity), which can potentially bias conclusions of the species’ demographic history ( Thalmann et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Oceanographic current systems, including the North and South China Coastal and Kuroshio Currents, shape the migration of marine and amphidromous species [6,15,53,54]. Previous studies have suggested that there were unlimited migrations between the South China Sea and the adjacent seas [7,16,55]. Within the South China Sea, previous studies also displayed unlimited migrations among populations [4,14,15,34,56].…”
Section: Genetic Structure and Diversitymentioning
confidence: 99%
“…Members of the PPSS, such as Ipomoea pes-caprae, Canavalia rosea, Vigna marina, Hibiscus tiliaceus, and H. pernambucensis are considered to have a global distribution through extremely long-distance seed dispersal. Genetic structure and phylogenetic relationships have been studied in these PPSS (Miryeganeh et al, 2014;Takayama et al, 2006Takayama et al, , 2008Vatanparast et al, 2011;Yamamoto et al, 2019), but the timing of the origin of PPSS and its global expansion processes were still unknown because of less mutations in the chloroplast markers used.…”
Section: Time Of Global Expansion Of Ppssmentioning
confidence: 99%